ETNOBOTANI TUMBUHAN BERGUNA OLEH MASYARAKAT SEKITAR KAWASAN KPH MODEL KAPUAS HULU (Studi Kasus Desa Tamao, Kecamatan Embaloh Hulu Kalimantan Barat) - Haryanti, Eva Sri; Diba, Farah; dina, Wah (Universitas Tanjungpura, 2015)
Tamao village, District EmbalohHulu, is one of thevillages in the district of Kapuas Hulu KPH model that has the potential of useful plants is very high. The study was conductedto determine the useful plant species utilized, the parts of the plant are used and useful plants for the benefit of society. Methods of data collection is done through interviews and question naires to determine the respondents using snowball sampling technique. Research carried out on surrounding communities KPH Model Kapuas Hulu district, in the village of Tamao, District Embaloh Hulu earn as much as 245 plant species from 85 families, and divided into eleven groups of uses, namely food plants (116 species), medicine (150 species), dyes (19 species), fodder(17 species), ornamental plants (94 species), craft materials (21 species), pesticide plant (12 species), aromatics (18 species), firewood (13 species), building materials (19 species) and for customs purposes (58 species). Family that is widely use disthe family Fabaceae. Plant species are widely used in eleven usability include Pandan (Pandanus amaryllifolius) 6 usability and Beletik (Nephelium lappaceumL) 5 usability. Keywords: Ethnobotany useful plants, KPH Model Kapuas Hulu, Â Snowball sampling